The Association between Adiponectin, Insulin and Troponin I in Patients with Acute Myocardial Infarction - Ibrahim, Ammal Esmaeel; El-Yassin, Hadef Dhafer; Al-Janabi, Hamid Kareem Sachit (Al-Nahrain Journal of Science, 2012)
Adipose tissue is increasingly recognized as a key regulator of energy balance, playing an active role in lipid storage and buffering, and synthesizing and secreting a wide range of endocrine products that may be directly involved in the pathogenesis of the complications associated with obesity the most important adiposcyte deviated hormone is adiponectin. Insulin is a hormone that is central to regulating the energy and glucose metabolism in the body. Troponin is a complex of three regulatory proteins that is integral to muscle contraction in skeletal and cardiac muscle.This study was conducted during the period from Decenber2009 to April 2010, includes fifty patients with Acut Myocardial Infarction (AMI) were admitted to Cardiac Care Unit (CCU) at Medical City Teaching Hospital and Ibn –ALbetar Hospital in Baghdad. Levels of adiponectin, insulin and troponin were measured by ELISA method.The levels of adiponectin, insulin and troponin were significantly elevated with (p<0.001), A negatively significant correlation between adiponectin with insulin and troponin in acute myocardial infarction patients was found.Adiponectin was negatively associated with insulin in patients with AMI